The Assessment of Relations between Socioeconomic Status and Number of Complications among Type 2 Diabetic Patients - B Mohebbi; M Mahmoodi; D Shojaeezadeh; A Pourreza; A Tol (Tehran University of Medical Sciences, 2012)
Background:The prevalence of diabetes mellitus among Iranian aged 25-64 estimated to be about 7.7%.The aim of current study was the assessment of socioeconomic status of diabetic patients and their complications.Methods:A cross sectional study was conducted on type 2 diabetic patients with complications in four major teaching hospitals affiliated to Tehran University of Medical Sciences (TUMS) during July 2009 to March 2010. All patients (530) were interviewed through a questionnaire with 85% response rate (450 patients). Skilled nurses were assigned as responsible for data collection. Collected data analyzed by Exact Fisher and χ2 tests using SPSS version 11.5.Results: The majority of patients had experienced one or more complications. Findings revealed that 50%, 33.6% and 16.4% of the patients suffered from one, two, and three complications of type 2 diabetes, respectively. Patients with cardiovascular complications included 22.2%, with both cardiovascular and eye complications (12.7%), and with cardiovascular, eye and foot ulcer together 14% of the respondents. Frequency of complications demonstrated significant relation with sex,age,educational level,type of occupation, duration of diabetes (P<0.001) and social class (P=0.002).The majority of patients (54.2%) belonged to low income group.Conclusion: It seems patients with low socioeconomic status face more challenges in their social environment together with less psychological support. Health care systems are responsible to empower them to control their illness and feel a better life to live.